Investigating the Meraka Hardwood Failure in Bolted Connections Parallel to the Timber Grain - Razak Abdul Karim, Abdul; Quenneville, Pierre; M.Saâ€™don, Norazzlina; Yusof, Mahshuri (International Journal of Engineering and Technology, 2018)
The present study was performed to investigate the ductile failure mode of timber bolted connections, specifically in Meraka hardwood. This was done to initiate an effort in developing a comprehensive guideline in designing the timber bolted connections for the purpose of strengthening the wall-diaphragm connections of the Malaysia unreinforced masonry buildings. A series of experimental tests was conducted on the steel-wood-steel (SWS) with a single row connection type. A total of eight different bolted connection configurations or groups with ten replicates for each group was tested. The Meraka hardwood was selected in this study as it was found to be one of the most hardwood species that are commonly used in the construction of floor and roof diaphragms in the existing Malaysia unreinforced masonry buildings. From the experimental results obtained, the effectiveness of the Malaysian timber code of MS544 and European Yield Model (EYM) in predicting the bolted connection strength was verified. It was determined that the MS544 is too conservative in estimating the bolted connection strength with an average ratio of 0.38 compared to the test results. Thus, the use of the EYM is recommended to complement the timber code as the average ratio of 0.81 was identified in comparison to the test data.Â Â